A Review of Tools to Calculate the Cost of Health Conditions and Common Health Risk Factors. (November 2015) - Contreary, Kara; Chen, Zhuo (Adam); Chattopadhyay, Sajal; Chang, Man-Huei
Abstract : A cost calculator is a software tool that calculates the monetary cost associated with a disease, condition, or risk factor within a population group. We attempted to identify all available public health cost calculators using adapted systematic review methodology and performed a qualitative and a quantitative review on each included calculator. We first abstracted each calculator to ascertain its subject, target user, methodology, and output. We also developed a novel set of scoring criteria and evaluated each calculator for transparency and customizability. We found a wide variety of existing calculators in terms of subject area, target user, and analytic methodology. Furthermore, using our rating criteria, we found large differences in transparency with respect to the assumptions and parameter inputs driving results. Abstract : This article provides a review of select cost calculators used in public health, a set of practical criteria used in evaluating such tools, and a systematic assessment of existing cost calculators.